Using Feathers for Molecular Sexing of Straw-headed Bulbul (Pycnonotus zeylanicus) Offsprings - Pramana Yuda; Worawidh Wajjwalku (Journal of Tropical Biodiversity and Biotechnology, 2022)
Sex determination of of straw-headed bulbul offspring was carried out from 27 offspring’s plucked feather samples in a captive breeding program. Using direct PCR, this study provided more evidences that feather samples are reliable as a source of DNA for non-invasive and effective molecular sexing. The study also revealed that the offspring sex ratio of straw-headed bulbul was slightly inclined towards males, but there was no significant difference from the value of 0.5.